EMPIRICAL EVIDENCE OF ENTREPRENEURIAL COMPETENCIES AND FIRM PERFORMANCE: A STUDY OF WOMEN ENTREPRENEURS OF NIGERIA - Mohammed, Kabir; Ibrahim, Hazril Izwar; Mohammad Shah, Khairul Anuar (De Gruyter Open, 2017)
The purpose of current study is to investigate the effects of entrepreneurial competencies on firm performance of businesses owned by Nigerian women entrepreneurs. The 200 respondents of this study are women entrepreneurs operating micro-business units in Kaduna state, Nigeria. Survey questions was used to collect data. The study utilises SPSS and SmartPLS 2.0 to analyse the data. The findings indicated that strategic, opportunity and organizing competencies significantly affect the firm performance of women entrepreneurs in Nigeria.